Positive impact of insulin treatment on clinical trend in cystic fibrosis patients: a retrospective study - Giugno, Andrea; Leonardi, Salvatore; Lo Presti, Donatella; Timpanaro, Tiziana; Parisi, Giuseppe Fabio; Papale, Maria; Rotolo, Novella; Manti, Sara; Caruso-Nicoletti, Manuela (Acta Biomedica Atenei Parmensis, 2022)
Background Cystic fibrosis related diabetes is a complication of cystic fibrosis (CF). Aim of our study was to evaluate the effects of insulin therapy in overt diabetics or pre-diabetics CF patients on BMI and respiratory function. Methods We selected a sample of 17 insulin treated patients (Group T) and a sample of 17 CF control patients with normal glucose metabolism (Group C). Group T was also subdivided into overt diabetic patients and pre-diabetic patients (IGT, INDET). For treated patients an observation period was established from the first insulin administration to 12 months. For control patients, a comparable year of observation was chosen. Data regarding BMI, FVC, FEV1 and PEF were collected at time 0, and at time 12. The number of hospital admissions for infectious episodes during the year of observation and during the preceding year were recorded for Group T patients. Results The results showed a significant increase in BMI in treated patients compared to control, specially for overt diabetics. The study of spirometric parameters showed a significant improvement of PEF, the main effort-dependent respiratory index, specially for over diabetics, suggesting a hypothetical positive impact of the insulin anabolic action on the magnitude of expiratory effort. In contrast, the study of infectious episodes revealed a significant reduction of hospital admissions in pre diabetic treated patients. Conclusion Overall, our study focuses on the importance of glycemic monitoring during the early stages of CF disease and on the advantage of insulin treatment in the early stages of glucose alteration .